Training on Making Lightweight Concrete Using Hazelnut Shell Waste Aggregate for Brick Press Craftsmen - Mohammad Junaedy Rahman; Moeh. Kay Muddin Asnur; Ahnaf Riyandirga Ariyansyah Putra Helmy; Iriandy Iriandy (Jurnal Sipakatau: Inovasi Pengabdian Masyarakat, 2024)
This Community Service Program (PKM) aims to utilize candlenut shell waste as additional aggregate in the manufacture of pressed bricks, providing an innovative solution for waste management while supporting sustainable development. Candlenut shell waste, which is abundant but often thrown away, is processed into environmentally friendly construction materials. Training was provided to brick craftsmen in Makassar to introduce new methods that can improve the quality and mechanical strength of bricks, including compressive strength and thermal insulation properties.The training activities lasted for six months, covering the preparation, implementation, and evaluation stages. Participants were trained on how to mix candlenut shell waste with other raw materials, molding techniques, and the curing process to ensure product quality. As a result, candlenut shell-based bricks have a lighter weight and competitive quality compared to conventional bricks, while providing ecological benefits by reducing the environmental footprint. The positive response from the community shows great potential for further development, including product variations and business opportunities based on this innovation. With continued support, this program not only improves community skills but also encourages collaboration to create real social and economic impacts, making waste management part of the green development solution